Antimicrobial activity of the aqueous extract of selected Malaysian herbs - Zakaria, Zainul Amiruddin; Zakaria, M. L.; Amom, Zulkhairi; Mohd Desa, Mohd Nasir (Academic Journals, 2011)
Malaysia is rich in biodiversity encompassing a variety of herbs and shrubs with potential medicinal properties. Tinospira crispa (Patawali), Anacardium occidentale (Gajus),Garcinia atroviridis (Asam gelugor) and Hibiscus cannabinus (Kenaf) are some of the well-known local Malay herbs that have been studied for their medicinal applications. The objective of the present study was to evaluate the broad spectrum-antimicrobial effects of the aqueous extract of T. crispa, A. occidentale, H. cannabinus and G. atroviridis againstStaphylococcus aureus ATCC 25923 (Gram positive) and Escherichia coli ATCC 25922 (Gram negative) bacteria using the disc diffusion method. From the results obtained, all extracts were found to exhibit a similar inhibition zone of approximately 8.67-9.67 mm against both test organisms. Furthermore, the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of the respective extract for both test organisms were similar; 227.27 mg/ml for T. crispa and A. occidentale, 113.64 mg/ml for H. cannabinus, and 56.82 mg/ml for G. atroviridis. In conclusion, the selected plants exhibited antimicrobial activity wherein the effectiveness (indicated by low MBC value) was in the sequence of G. atroviridis, H. cannabinus, T. crispa and A. occidentale. This findings support the traditional use of these plants in the treatment of bacterial infection.